Abrasion resistance and compressive strength of unprocessed rice husk ash concrete - Djamaluddin, Abdul Rachman; Caronge, Muhammad Akbar; Tjaronge, M. W.; Md. Noor, Nurazuwa; Rahim, Irwan Ridwan (Springer Nature, 2018)
This paper investigates the effects of adding natural rice husk ash collected from uncontrolled burning and without previous grinding (NRHA) as cement replacement in concrete. To obtain an adequate particle size, NRHA was mixed with coarse aggregate for a convenient period of time before adding the other components. Compressive strength, water absorption, porosity, and abrasion resistance expressed as weight loss were examined. Test results show that decreasing the particle size through mixing with coarse aggregate improved the compressive strength, reduced the permeability, and increased the abrasion resistance of concrete. By mixing NRHA with aggregate for 8 min, abrasion resistance improved by 10.35 and 23.62% over the control concrete at 28 and 91 days, respectively. Incorporating NRHA in concrete by grinding with coarse aggregate during the mixing process could be suitable for making normal-strength concrete and for applications where abrasion resistance is an important parameter. In addition, using NRHA as a partial replacement cement contributes to the reduction of CO2 emissions due to the production of cement.